1973
DOI: 10.1017/s0022029900014369
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of volatile substances associated with Cheddar-cheese aroma

Abstract: A method for obtaining distillates from whole Cheddar cheese is described. The distillate has an aroma at -80 °C closely resembling that of the cheese before distillation. Gas chromatograms of the distillate were obtained by sampling the vapour over the distillate at -80 °C, using both a 15-m Apiezon surface-coated open tubular column and a 1-5-m glass column packed with Porapak Q. The aroma of the effluent was evaluated and the chromatograms simultaneously recorded by passing the vapour through a splitting de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Manning and Robinson (1973) reported that H 2 S, methanethiol, dimethylsulfide, diacetyl, methyl ketones, and volatile fatty acids play important roles in Cheddar cheese flavor. Sulfur compounds, such as dimethyl disulfide, which originate from methionine, generally have low odor threshold values and powerful odors, which are described as "sulfurous" and "cabbage-", "onion-", or "garlic-like".…”
Section: Methyl Ketones Have Been Identified In Cheddar Cheesementioning
confidence: 99%
“…Manning and Robinson (1973) reported that H 2 S, methanethiol, dimethylsulfide, diacetyl, methyl ketones, and volatile fatty acids play important roles in Cheddar cheese flavor. Sulfur compounds, such as dimethyl disulfide, which originate from methionine, generally have low odor threshold values and powerful odors, which are described as "sulfurous" and "cabbage-", "onion-", or "garlic-like".…”
Section: Methyl Ketones Have Been Identified In Cheddar Cheesementioning
confidence: 99%
“…
Recent Ivork on Cheddar cheese flavour has implicated methane thiol (CH,SH) as an important constituent of Cheddar aroma (Manning & Robinson, 1973;Manning, 1974). To determine whether this compound might be a metabolite of the bacterial flora of the cheese, isolates from milk and Cheddar cheese were examined for their ability to produce methane thiol.
…”
mentioning
confidence: 99%
“…studied the formation of methanethiol in Cheddar cheese and concluded that it was unlikely to be the product of bacteria or their enzymes. Methanethiol has been identified in cheese by , , Manning and Robinson (1973), Manning (1974), and Manning and Moore (1979). Manning (1974) showed a strong relationship between the concentration of methanethiol in the headspace and the flavor intensity of Cheddar cheese.…”
Section: Flavor Chemistry 91mentioning
confidence: 99%